ICSH recommendations for the standardization of nomenclature and grading of peripheral blood cell morphological features. (2nd March 2015) - Palmer, L.; Briggs, C.; McFadden, S.; Zini, G.; Burthem, J.; Rozenberg, G.; Proytcheva, M.; Machin, S. J.
Summary These guidelines provide information on how to reliably and consistently report abnormal red blood cells, white blood cells and platelets using manual microscopy. Grading of abnormal cells, nomenclature and a brief description of the cells are provided. It is important that all countries in the world use consistent reporting of blood cells. An international group of morphology experts have decided on these guidelines using consensus opinion. For some red blood cell abnormalities, it was decided that parameters produced by the automated haematology analyser might be more accurate and less subjective than grading using microscopy or automated image analysis and laboratories might like to investigate this further. A link is provided to show examples of many of the cells discussed in this guideline.